Quantum graph spectra of a graphyne structure - Do, Ngoc T.; Kuchment, Peter (Nanoscale systems mathematical modeling, theory and applications, 2013)
We study the dispersion relations and spectra of invariant Schrödinger operators on a graphyne structure (lithographite). In particular, description of different parts of the spectrum, band-gap structure, and Dirac points are provided.